2019
DOI: 10.1016/j.ympdx.2019.100005
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Counts in Healthy South African Infants: Implications for Enrollment and Adverse Event Grading in Clinical Trials in an African Setting

Abstract: Absolute neutrophil counts are used to assess eligibility and safety during clinical trials but the toxicity grading scale used can affect enrollment and reporting of adverse events. During a trial investigating a parenteral rotavirus vaccine in South Africa, we excluded otherwise healthy infants without HIV infection from participation owing to neutropenia. Trial registration ClinicalTrials.gov : NCT02109484 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Abnormalities in hematological parameters, including ANC, are used to evaluate the eligibility of volunteers to participate in clinical trials and to assess any emerging safety signals during the conduct of the trial. Misclassification of ANC values may affect enrollment and might also lead to incorrect interpretation of the safety profile of a pharmaceutical product [ 19 ]. During the conduct of the S. sonnei 1790GAHB vaccine studies, transient and clinically asymptomatic neutropenia events have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in hematological parameters, including ANC, are used to evaluate the eligibility of volunteers to participate in clinical trials and to assess any emerging safety signals during the conduct of the trial. Misclassification of ANC values may affect enrollment and might also lead to incorrect interpretation of the safety profile of a pharmaceutical product [ 19 ]. During the conduct of the S. sonnei 1790GAHB vaccine studies, transient and clinically asymptomatic neutropenia events have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Reference ranges previously obtained from non-African populations may, therefore, have limited applicability to populations of African ethnicity in clinical practice or research [ 9 , 10 ]. A previous study demonstrated that an additional 16% of potentially eligible, healthy participants were excluded from participation in a rotavirus vaccine clinical trial on the basis of neutropenia because reference ranges inappropriate for the study population were used in their assessment [ 11 ]. The use of inappropriate reference ranges in clinical trials to determine participant eligibility may result in the underrepresentation of this population in research.…”
Section: Introductionmentioning
confidence: 99%